2018
DOI: 10.1002/anie.201810122
|View full text |Cite
|
Sign up to set email alerts
|

Isovalent Cation Ordering in the Polar Rhombohedral Perovskite Bi2FeAlO6

Abstract: Ordering of cations in different structural types occurs when there is a significant difference in the oxidation states and ionic radii of the ions involved. Herein we report an unusual ordering of isovalent cations Fe3+ and Al3+ in the polar rhombohedral R3 double perovskite structure of Bi2FeAlO6 synthesized at high‐pressure (6 GPa) and high‐temperature (1000 °C). This ordered structure is derived from the 1:1 combination of the polar oxides BiFeO3 (R3c) and BiAlO3 (R3c), which results in reduction of symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Recently, there has been considerable interest in bismuth-based perovskites of the type BiMO 3 (M = transition metals), which are potential candidates for materials exhibiting multiferroic properties. [17][18][19][20] Many of the bismuth compounds [BiMO 3 (where M = Cr, Mn, Co, or Ni)] require high pressures to stabilize the perovskite structure. For example, the high-pressure phase of BiMnO 3 is a widely studied material which has a monoclinic structure (C2/c) and shows ferromagnetic behavior with T C of 100 K. 18 In fact, it has been reported that oxygen non-stoichiometry plays a crucial role in determining the structure and properties of BiMnO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been considerable interest in bismuth-based perovskites of the type BiMO 3 (M = transition metals), which are potential candidates for materials exhibiting multiferroic properties. [17][18][19][20] Many of the bismuth compounds [BiMO 3 (where M = Cr, Mn, Co, or Ni)] require high pressures to stabilize the perovskite structure. For example, the high-pressure phase of BiMnO 3 is a widely studied material which has a monoclinic structure (C2/c) and shows ferromagnetic behavior with T C of 100 K. 18 In fact, it has been reported that oxygen non-stoichiometry plays a crucial role in determining the structure and properties of BiMnO 3 .…”
Section: Introductionmentioning
confidence: 99%